Estudo da compartimentalização da sGTPASES RAS e RAC1 em células da linhagem de tumores humanos de mama MAMA MDA-MB-231 mediante ativação por fontes endógenas e exógenas de óxido nítrico: associação com a migração celular - Strumillo, Scheilla Teixeira [UNIFESP] (2019)
Ras is a protein with GTPase activity expressed in all cells with high cell proliferation rates and despite the low frequency of mutated forms of RAS oncogene in breast cancer (less than 5%), there is evidence to suggest that hyperactivity of Ras oncogenic protein promotes the growth and development of this cancer. Like Ras, Rac1 is a GTPase and is targeted by Ras mediated signaling. Recent published studies have shown the involvement of Rac1 in the migration of breast tumors. The overall objective that guided the development of this project was to evaluate whether endogenous nitric oxide (NO) production by the MDA-MB-231 cell line, representative of triplenegative breast cancer, or exposure of these cells to an exogenous source of s-nitrosothiol snitrosoglutathione (GSNO) would stimulate cellular signaling through Ras GTPase and if this was a process that could occur in two cell compartments, the plasma membrane and the Golgi apparatus. Subsequently, we analyzed the involvement of GTPase Rac1, which is downstream in the Ras signaling pathway. We also wanted to determine whether the compartmentalization of this NO-mediated cell signaling process would be determinant for the migration and proliferation capabilities of the MDA-MB-231 tumor line. In our results we found that GSNO stimulated Ras activity in MDA-MB-231 cells, but did not stimulate the migration of these cells. Although GSNO treatment stimulated cell viability, MDA-MB-231 cell proliferation increased slightly, results that we also observed after LPS stimulation. We speculate that the high baseline NO production in these cells is a critical factor in explaining the mild effects of NO donor on MDA-MB-231 cell proliferation. The stimulation of these cells with LPS resulted in endogenous NO production and compartmentalization of Rac1 to the perinuclear region after two hours of stimulation, a period that coincided with the stimulation of its activity. Our results also suggested that in MDA-MB-231 cells Ras was apparently resident in the perinuclear region. We concluded that endogenously produced NO, by stimulating cells with LPS, was determinant for the migration stimulus of MDA-MB-231 cells. In this signaling pathway associated with cell migration participate the Ras and Rac1 GTPases, iNOS, Src, PLC and Ca2+ ions.